Secure Data Transmission Protocols for Telehealth: Improving Encryption, Authentication, and System Resilience (Digital Health & Telemonitoring Advances E: 3117-6461 | P: 3117-647X, 2026)
The rapid expansion of telehealth systems has revolutionized healthcare delivery by enabling remote diagnosis, monitoring, and consultation. However, this transformation has introduced significant cybersecurity challenges, particularly in the secure transmission of sensitive patient data. Ensuring confidentiality, integrity, and availability of medical information is critical, as breaches can lead to severe privacy violations and compromised patient safety. This paper presents a comprehensive analysis of secure data transmission protocols in telehealth systems, with a focus on improving encryption mechanisms, authentication strategies, and system resilience. The study explores existing cryptographic frameworks, including symmetric and asymmetric encryption techniques, Transport Layer Security (TLS), and emerging lightweight cryptographic solutions tailored for resource-constrained devices. Additionally, it examines advanced authentication methods such as multi-factor authentication (MFA), biometric verification, and blockchain-based identity management systems. The paper further evaluates resilience strategies, including intrusion detection systems, fault tolerance, and secure network architectures, to mitigate cyber threats. Through a machine learning-informed perspective, the paper highlights opportunities for adaptive security mechanisms capable of detecting anomalies and dynamically responding to threats. The findings indicate that a layered security approach integrating encryption, authentication, and resilience mechanisms significantly enhances telehealth system security. Finally, the paper  outlines future research directions aimed at developing scalable, interoperable, and privacy-preserving telehealth infrastructures.